Evaluation of the microstructural and mechanical properties of ductile cast iron and alloy steel dissimilar materials welded by magnetically impelled arc butt - Mingjian Peng (Elsevier, 2021)
The combined use of ductile cast iron and alloy steel is beneficial, however, this technique causes some difficulties in welding due to the different properties of these two materials. In the present work, magnetically impelled arc butt (MIAB) welding a solid-state joining process, was employed to weld GGG40 ductile cast iron tube and an E355 + N alloy steel tube (each one had a thickness of 6 mm). The microstructure and mechanical properties of the resultant joints along different positions of the weld tube were systematically investigated. The heating during MIAB welding was non-uniform, causing significant changes in the microstructure, microhardness, and tensile stress of the welds. The maximum hardness of the welds (482 HV) was much higher than that of the base metal. The average (334.4 MPa) and maximum tensile strengths (382.4 MPa) of the welds were 83.6% and 95.6% of those of the base metal, respectively. These results show that MIAB is an effective method for welding ductile cast iron/alloy steel dissimilar materials.